2017
DOI: 10.1002/14651858.cd012651
|View full text |Cite
|
Sign up to set email alerts
|

Diet, physical activity and behavioural interventions for the treatment of overweight or obese children from the age of 6 to 11 years

Abstract: Multi-component behaviour-changing interventions that incorporate diet, physical activity and behaviour change may be beneficial in achieving small, short-term reductions in BMI, BMI z score and weight in children aged 6 to 11 years. The evidence suggests a very low occurrence of adverse events. The quality of the evidence was low or very low. The heterogeneity observed across all outcomes was not explained by subgrouping. Further research is required of behaviour-changing interventions in lower income countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
389
1
27

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 387 publications
(437 citation statements)
references
References 541 publications
20
389
1
27
Order By: Relevance
“…Severe obesity is a serious public health issue and the results of this study show that a large number of children in Europe suffer from it. Given its impact on education, health, social care, and the economy, obesity needs to be addressed via a range of approaches, from prevention to early diagnosis and treatment [65, 66]. …”
Section: Resultsmentioning
confidence: 99%
“…Severe obesity is a serious public health issue and the results of this study show that a large number of children in Europe suffer from it. Given its impact on education, health, social care, and the economy, obesity needs to be addressed via a range of approaches, from prevention to early diagnosis and treatment [65, 66]. …”
Section: Resultsmentioning
confidence: 99%
“…The current golden standard for tackling childhood weight problems is an outpatient, family-based multidisciplinary obesity treatment (MOT; Al-Khudairy et al, 2017;Mead et al, 2017). It primarily aims at a healthy lifestyle via changes in eating behaviour and physical activity, through cognitive behavioural techniques and parental involvement (Batterham, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses, however, showed limited effectiveness on weight loss [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%